Amorphous selenide with ultra-high cycle stability and preparation method and application thereof
The crystalline metal selenide is converted into amorphous form through low-temperature doping technology, which solves the structural collapse and volume expansion problems of crystal electrode materials during the circulation process, and achieves the preparation of ultra-high cycle stability amorphous selenide and good electrochemical performance.
Patent Information
- Application Number
- CN202311825109.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-12-28
- Publication Date
- 2025-03-07
- Estimated Expiration
- 2043-12-28
AI Technical Summary
The existing crystal selenide electrode materials have problems of structural collapse and volume expansion during the circulation process, resulting in poor energy storage performance. The preparation method usually requires high temperature and high pressure, and consumes high energy.
Through low-temperature doping technology, heteroatoms (such as oxygen, nitrogen, sulfur, and phosphorus) doping are used to destroy the lattice structure, and the crystalline metal selenide is transformed into amorphous form, realizing the preparation of ultra-high cycle stability amorphous selenide.
The high cycle stability and good electrochemical properties of amorphous selenide are achieved, and the structural stability and volume expansion problems of crystal electrode materials during the cycle are solved, and the preparation energy consumption is reduced.
Smart Images

Figure CN117776116B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of negative electrode materials, and in particular to an amorphous selenide with ultra-high cycle stability and a preparation method and application thereof. Background Art
[0002] In recent decades, with the depletion of fossil fuels and the increasingly serious environmental pollution problems such as the greenhouse effect, people have a high demand for clean and renewable energy, which has promoted the rapid development of advanced energy storage systems. Lithium, sodium, and potassium ion batteries stand out due to their advantages such as high energy density, high energy storage efficiency, long cycle life, and wide application range. Among many different candidate materials, people are increasingly interested in the application of layered transition metal dichalcogenides (TMDs) in the field of electrochemical energy storage due to their fascinating physical and chemical properties. They have a unique two-dimensional layered structure, including covalently bonded monolayers, which are bound together by weak van der Waals interactions. The interlayer channels can provide space for efficient and reversible ion storage. Among the many TMDs, metal selenides are favored as negative electrode materials for metal ion batteries because of their larger interlayer spacing and smaller band gap, good Coulombic efficiency, and higher electronic conductivity. In particular, its interlayer distance of the (002) plane is 6.40A, which is conducive to Li + 、Na + , K + Ions are easy to embed and extract, so good pseudocapacitive behavior is expected. However, crystalline electrodes also have some disadvantages: ① Limited ion channels for alkali metal ion insertion / extraction; ② The available capacity is limited by many factors, including crystal orientation, phase transition, exposed crystal surface and structural stability; ③ Electrode crushing during cycling leads to an unstable solid electrolyte interphase (SEI) layer. In contrast, isotropic amorphous materials have the unique advantages of faster diffusion kinetics, larger free volume and more active sites, which are ultimately conducive to accommodating Li + / Na + / K + The huge volume expansion that occurs during the (de)intercalation process has great potential to achieve superior electrochemical performance. If an amorphous electrode is combined with a metal selenide, more active sites can be obtained by utilizing the large number of defects in the amorphous material itself, as well as the high capacity advantage of the selenide itself, so that an electrode with faster ion transfer rate and higher capacity can be obtained. At present, the preparation of amorphous selenides is mainly through vacuum evaporation deposition, hydrothermal method, etc., but these methods are all high temperature and high pressure, which inevitably consumes a lot of energy and time, and how the crystalline material is transformed into an amorphous material in the next step under low temperature and short time conditions has not been reported. Therefore, it is of great significance to explore the transformation of crystalline materials to amorphous materials, and it is very desirable to replace amorphous electrode materials for low-cost battery systems. Summary of the invention
[0003] In view of the above-mentioned prior art, the purpose of the present invention is to provide an ultra-high cycle stability amorphous selenide and its preparation method and application. The amorphous metal selenide negative electrode material prepared by the present invention has the advantages of many active sites, fast ion diffusion rate, extremely small volume expansion and good stability, and can be used as a new strategy to improve the electrochemical performance of secondary ion battery negative electrode materials.
[0004] To achieve the above object, the present invention adopts the following technical solution:
[0005] The first aspect of the present invention provides a method for preparing the above-mentioned ultra-high cycle stability amorphous selenide, the preparation method comprising:
[0006] The crystalline metal selenide is doped with a heteroatom source capable of forming a doping atmosphere to obtain an amorphous heteroatom-doped metal selenide, that is, an amorphous selenide with ultra-high cycle stability.
[0007] Preferably, the doped heteroatom is at least one of O, N, S, and P; and the heteroatom source is air, oxygen, ammonia, hydrogen sulfide, or sodium phosphite.
[0008] More preferably, the heteroatom source is air or oxygen.
[0009] Preferably, the doping is low-temperature doping, the temperature of the low-temperature doping is 100-350° C., and the time of the low-temperature doping is 0.5-3 h.
[0010] Preferably, the crystalline metal selenide is prepared by the following method:
[0011] (1) dissolving a polyoxometalate in a mixture of ethanol and water under stirring at room temperature to obtain a polyoxometalate solution, adjusting the pH value of the polyoxometalate solution to neutral or alkaline, and then adding a dopamine hydrochloride solution to react to obtain metal-polydopamine;
[0012] (2) Selenide the metal-polydopamine with selenium powder in an inert atmosphere to obtain a crystalline metal selenide.
[0013] Preferably, in step (1), the volume ratio of ethanol to water is 1:(1-10); the pH value is adjusted to 7-10; and the metal in the polyoxometalate is tungsten, molybdenum, vanadium, niobium or tantalum.
[0014] Preferably, in step (1), the volume ratio of the polyoxometalate solution to the dopamine hydrochloride solution is 2-4:1; the concentration of the dopamine hydrochloride solution is 1.9-2.1 mg / mL; the ratio of the amount of the added polyoxometalate to dopamine hydrochloride is 0.2-0.4 mmol:0.1 mmol; and the reaction time is 24 h.
[0015] Preferably, in step (2), the mass ratio of the metal-polydopamine to selenium powder is 1:1-5; and the inert atmosphere is a hydrogen-argon mixed gas, argon or nitrogen.
[0016] Preferably, in step (2), the temperature of selenization is 500-800° C., and the time of selenization is 1-3 hours.
[0017] In a second aspect of the present invention, an ultra-high cycle stability amorphous selenide is provided. The amorphous selenide is obtained by doping a crystalline selenide with heteroatoms, wherein the amount of heteroatoms doped in the amorphous selenide is 10 to 20 at%, and the heteroatom source is air, oxygen, ammonia, hydrogen sulfide or sodium phosphite.
[0018] Preferably, the heteroatom source is air or oxygen.
[0019] The third aspect of the present invention provides the use of amorphous selenide with ultra-high cycle stability in the preparation of energy storage devices.
[0020] Beneficial effects of the present invention:
[0021] (1) The present invention is the first to propose a method of using heteroatom doping to destroy the lattice structure to transform it into an amorphous material, thereby realizing a one-step transformation of crystalline materials into amorphous materials. The method of the present invention is simple to operate and provides a new idea for the transformation of other crystalline materials into amorphous materials.
[0022] (2) The disordered structure of the amorphous material of the present invention has more ion storage sites such as lithium, sodium, and potassium, which is conducive to the rapid diffusion of ions and thus has better energy storage performance. In the conversion reaction of the battery, its amorphous nature has a lower activation energy barrier for structural rearrangement, thereby greatly improving the electrochemical performance of the amorphous metal selenide electrode material in secondary alkali metal ion batteries.
[0023] (3) The present invention destroys the crystal structure through oxygen and transforms it into a disordered amorphous state, thereby increasing the migration rate of ions, alleviating the mechanical strain stress of the material during the cycle of the secondary rechargeable battery, and solving the problem of structural collapse and volume expansion of layered transition metals during the cycle. The large specific capacity better meets the development needs of battery industrialization and has great application prospects. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1The oxygen-doped amorphous MoSe prepared in Example 1 x Scanning electron microscopy (SEM) images of the materials;
[0025] Figure 2 The oxygen-doped amorphous MoSe prepared in Example 1 x X-ray diffraction pattern (XRD) of the material;
[0026] Figure 3 The oxygen-doped amorphous MoSe prepared in Example 1 x High magnification transmission electron microscope (HRTEM) of the material;
[0027] Figure 4 Schematic diagram of the application of the material in sodium ion batteries, wherein 1 is a 2032 model battery shell, 2 is nickel foam, 3 is a sodium sheet, 4 is a sodium ion battery separator, and 5 is the material prepared in Example 1;
[0028] Figure 5 The electrode materials in Example 1 and Comparative Example 1 are 0.5A·g -1 Comparison of cycle performance at current density;
[0029] Figure 6 The electrode material of Example 1 is at 10A·g -1 The charge and discharge curve of 1000 cycles at a current density of;
[0030] Figure 7 The crystalline MoSe prepared in Comparative Example 2 x X-ray diffraction pattern (XRD) of the material;
[0031] Figure 8 The crystalline MoO prepared in Comparative Example 3 x X-ray diffraction pattern (XRD) of the material. DETAILED DESCRIPTION
[0032] It should be noted that the following detailed descriptions are illustrative and are intended to provide further explanation of the present application. Unless otherwise specified, all technical and scientific terms used herein have the same meanings as those commonly understood by those skilled in the art to which the present application belongs.
[0033] As introduced in the background technology section, the development of layered transition metal materials is restricted by a variety of disadvantages, such as low capacity caused by limited ion channels and large volume expansion, as well as slow ion transport rate.
[0034] Based on this, the purpose of the present invention is to provide an ultra-high cycle stability amorphous selenide and its preparation method and application. The present invention is the first to propose a metal selenide electrode material that utilizes oxygen doping-induced crystal to amorphous conversion. First, polyoxometalate and dopamine hydrochloride are mixed, and dopamine hydrochloride undergoes self-polymerization under weak alkaline conditions. Dopamine hydrochloride has a large number of hydroxyl groups and amino groups, which can chelate and adsorb transition metal ions and oxygen-containing metal ions during the self-polymerization process to form metal-polydopamine. Secondly, selenium is doped into metal-polydopamine by selenium sublimation to form metal selenide. During the selenization process, the material morphology is always a flower ball structure composed of nanosheets, where polydopamine is then converted into a carbon coating layer to wrap the main selenide under high temperature conditions, thereby improving the conductivity of the material. Finally, by low-temperature doping, oxygen in the air is used to destroy the lattice structure of the metal selenide to obtain an amorphous oxygen-doped metal selenide, and the carbon coating layer formed in the previous step is still coated on the outer layer of the amorphous material, so its morphology is still a flower ball structure composed of nanosheets. The low-temperature doping time and temperature of the present invention control the transformation of the crystalline form to the amorphous form: if the doping time is too short, it is not enough to transform the crystalline metal selenide into the amorphous form; if the doping time is too long, the metal selenide will transform from the amorphous form to the crystalline form. Only when the heteroatom doping amount is controlled within the range of 10-20%, can the amorphous selenide be formed.
[0035] The present invention breaks the traditional method of preparing amorphous materials and realizes reverse synthesis - transformation from crystal to amorphous. The amorphous material prepared by the present invention has very good application in energy storage devices. The disordered structure of amorphous selenide has more ion active sites and lower ion diffusion barriers, which enhances the diffusion and storage of ions. The disordered structure has negligible volume expansion, low lattice strain, good structural stability and fast reaction kinetics, thereby greatly improving the electrochemical performance of amorphous selenide electrode materials in secondary ion batteries.
[0036] In order to enable those skilled in the art to more clearly understand the technical solution of the present application, the technical solution of the present application will be described in detail below in conjunction with specific embodiments.
[0037] The test materials used in the examples of the present invention are all conventional test materials in the art and can be purchased through commercial channels.
[0038] Example 1
[0039] (1) Preparation of Mo-polydopamine: Under stirring at room temperature, ammonia water was added dropwise to 30 mL of alcohol-water mixture (10 mL of ethanol + 20 mL of water) containing 0.4 mmol of phosphomolybdic acid to adjust the solution pH to 8. Subsequently, 10 mL of a 2 mg mL -1The dopamine hydrochloride solution was stirred for 24 hours and the color of the solution finally turned dark red. The sample was collected by centrifugation and washed three times with ethanol and dried in an oven at 60°C for one night to obtain Mo-polydopamine.
[0040] (2) Preparation of crystalline MoSe2: 1 g Mo-polydopamine and 3 g selenium powder were placed in a tube furnace and calcined at 600 °C for 2 h in an argon-hydrogen atmosphere at a heating rate of 2 °C / min to obtain crystalline MoSe2.
[0041] (3) Low-temperature oxygen doping induces the transformation of crystal to amorphous state: Crystallized MoSe x Place it in a tube furnace and calcine it at 300°C for 0.5h in air with a heating rate of 3°C / min to obtain oxygen-doped amorphous MoSe2.
[0042] The scanning electron microscope photograph of the amorphous oxygen-doped MoSe2 structure prepared in Example 1 is as follows Figure 1 As shown, the phase of the obtained sample was tested by X-ray diffraction ( Figure 2 ), it can be seen that the material does not have an obvious crystallization peak, but is composed of a wider bulge, which is the characteristic peak of amorphous materials. Therefore, it can be seen that the phase structure of the prepared material is amorphous oxygen-doped selenide. In order to verify the above results, the material was tested at a high magnification transmission ( Figure 3 ), it can be seen from the picture that there are indeed no lattice fringes in the material, proving the successful synthesis of amorphous oxygen-doped selenide. Under this condition, the oxygen doping amount is 15at%. Figure 4 Schematic diagram of the application of the material in secondary ion batteries, wherein 1 is a 2032 model battery shell, 2 is nickel foam, 3 is an alkali metal sheet, 4 is a battery separator, and 5 is amorphous oxygen-doped MoSe2 (negative electrode material) prepared in Example 1. Figure 5 The electrode material is 0.5Ag in sodium ion batteries -1 The charge and discharge curves of 1000 cycles at a current density of .
[0043] Example 2
[0044] (1) Preparation of W-polydopamine: Under stirring at room temperature, ammonia water was added dropwise to 30 mL of alcohol-water mixture (10 mL of ethanol + 20 mL of water) containing 0.4 mmol of phosphotungstic acid to adjust the solution pH to 8. Subsequently, 10 mL of a 2 mg mL -1 The dopamine hydrochloride solution was stirred for 24 hours and the color of the solution finally turned dark red. The sample was collected by centrifugation and washed three times with ethanol and dried in an oven at 60°C overnight.
[0045] (2) Preparation of crystalline WSe2: 1 g W-polydopamine and 3 g selenium powder were placed in a tubular furnace and calcined at 600 °C for 2 h in an argon-hydrogen atmosphere with a heating rate of 2 °C / min to obtain crystalline WSe2.
[0046] (3) Low-temperature oxygen doping induces the transformation of crystal to amorphous state: The crystallized WSe2 is placed in a tube furnace and calcined at 300°C for 0.5 h in air at a heating rate of 3°C / min to obtain oxygen-doped amorphous WSe2. Under this condition, the oxygen doping amount is 15 at%.
[0047] Comparative Example 1
[0048] (1) Preparation of Mo-polydopamine: Under stirring at room temperature, ammonia water was added dropwise to 30 mL of alcohol-water mixture (10 mL of ethanol + 20 mL of water) containing 0.4 mmol of phosphomolybdic acid to adjust the solution pH to 8. Subsequently, 10 mL of a 2 mg mL -1 The dopamine hydrochloride solution was stirred for 24 hours and the color of the solution finally turned dark red. The sample was collected by centrifugation and washed three times with ethanol and dried in an oven at 60°C overnight.
[0049] (2) Preparation of crystalline MoSe2: 1 g Mo-polydopamine and 3 g selenium powder were placed in a tube furnace and calcined at 600 °C for 2 h in an argon-hydrogen atmosphere at a heating rate of 2 °C / min to obtain crystalline MoSe2.
[0050] Figure 5 The cycling performance of amorphous oxygen-doped MoSe2 prepared in Example 1 and crystalline MoSe2 prepared in Comparative Example 1 in sodium ion batteries is compared. It can be seen that at a current density of 0.5A -1 After 300 cycles, the specific capacity of amorphous oxygen-doped MoSe2 in Example 1 is 640.95 mAh g -1 , while the specific capacity of crystallized MoSe2 in comparative example 1 is 400.72 mAh g -1 , the performance of amorphous oxygen-doped MoSe2 is much better than that of crystalline MoSe2. Figure 6 Example 1 Amorphous oxygen-doped MoSe2 in 10Ag -1 From the performance diagram after 1000 cycles of charge and discharge under high current density, it can be seen that amorphous oxygen-doped MoSe2 still has good electrochemical properties and ultra-high capacity under high current density.
[0051] Comparative Example 2
[0052] The difference from Example 1 is that the calcination time in step (3) is 0.25 h. The XRD pattern of the MoSe2 finally obtained is shown in Figure 7It can be seen that MoSe2 is a crystalline structure at this time, and the oxygen doping amount under this condition is 5at%. This indicates that the low-temperature induction time is too short to transform the crystalline structure into the amorphous structure.
[0053] Comparative Example 3
[0054] The difference from Example 1 is that the calcination time in step (3) is 4 h. The XRD pattern of the MoO3 finally obtained is as follows: Figure 8 As shown, it can be seen that due to the long temperature, oxidation is very serious. Under this condition, the oxygen doping amount is 35at%. The material becomes crystalline MoO3. This shows that under long-term oxidation conditions, amorphous MoSe2 is transformed into crystalline MoO3.
[0055] The above description is only the preferred embodiment of the present application and is not intended to limit the present application. For those skilled in the art, the present application may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present application shall be included in the protection scope of the present application.
Claims
1. Use of ultra-high cycle stability amorphous selenide in the preparation of energy storage devices, characterized in that: The preparation method of the ultra-high cycle stability amorphous selenide is: A crystalline metal selenide is doped at low temperature with a heteroatom source capable of forming a doping atmosphere to obtain an amorphous heteroatom-doped metal selenide, i.e., an amorphous selenide with ultra-high cycle stability; the doped heteroatom is O; the heteroatom source is air; the temperature of the low temperature doping is 300° C., and the time of the low temperature doping is 0.5-3 hours; The heteroatom doping amount in the amorphous selenide is 10-20 at %; the crystalline metal selenide is crystalline MoSe2 or crystalline WSe2; The crystalline metal selenide is prepared by the following method: (1) Under stirring at room temperature, adjusting the pH value of the alcohol-water mixture of polyoxometalate to neutral or alkaline, and then adding dopamine hydrochloride solution to react to obtain metal-polydopamine; (2) Selenizing the metal-polydopamine with selenium powder in an inert atmosphere to obtain a crystalline metal selenide; The energy storage device is a sodium ion battery.
2. The use according to claim 1, characterized in that In step (1), the alcohol-water mixture is a mixture of ethanol and water; the volume ratio of ethanol to water is 1:(1-10); the pH value is adjusted to 7-10; and the metal in the polyoxometalate is tungsten or molybdenum.
3. The use according to claim 1, characterized in that In step (1), the volume ratio of the polyoxometalate solution to the dopamine hydrochloride solution is 2-4:1; the concentration of the dopamine hydrochloride solution is 1.9-2.1 mg / mL; the ratio of the added amounts of the polyoxometalate and dopamine hydrochloride is 0.2-0.4 mmol:0.1 mmol; and the reaction time is 24 h.
4. The use according to claim 1, characterized in that In step (2), the mass ratio of the metal-polydopamine to selenium powder is 1:1-5; and the inert atmosphere is a hydrogen-argon mixed gas, argon or nitrogen.
5. The use according to claim 1, characterized in that: In step (2), the temperature of selenization is 500-800° C., and the time of selenization is 1-3 hours.
Citation Information
Patent Citations
Molybdenum diselenide hollow microspheres as well as preparation method and application thereof
CN116789083A
Systems and methods for universal degenerate p-type doping with monolayer tungsten oxyselenide (TOS)
US20210328021A1